Mentorship/methodology: reflections, praxis, futures - Gruwell, Leigh, editor; Lesh, Charles N., editor; Utah State University Press, publisher (Colorado State University. Libraries, 2024)
Sees mentorship as the location where the future of writing studies is invented and where the past is reproduced by bringing the two discrete concepts of mentorship and methodology together, inhabiting and theorizing the spaces and moments where they collide.--Provided by publisher.
Embodying cultural rhetorics methodology through mentorship / Elise Dixon, Trixie Smith, and Malea Powell -- The twilight of the methodology course, or How I learned to tell the tale and leave it / Brad Lucas -- Gentefying or gentrifying? Mentoring up to code on the methodological block / Eric A. House, Kelly Medina-López, and Kellie Sharp-Hoskins -- The legacy of care: origins and expectations of mentoring in writing center methodologies / Devon Fitzgerald Ralston -- Building research trajectories through mutual multi-generational mentoring in writing program assessment / Gregory J. Palermo, Qianqian Zhang-Wu, Devon Skyler Regan, and Mya Poe -- Expanding the WAC network: the cross-institutional mentoring project / Alisa Russell and Thomas Polk -- Professionalizing mentorship: the new ethos of academic publishing / Jessica Clements and John Pell -- Slow mentorship: a feminist methodology for un/becoming / Lesley Erin Bartlett, Jessica Rivera-Mueller, and Sandra L. Tarabochia -- Who mentors the mentors? How writing center pedagogy, labor, and administrator status impact methodologies / Elizabeth Geib Chavin and Beth A. Towle -- Rethinking mentorship through institutional ethnography and writing center pedagogy: mapping up to engage in transformative work / Anna Sicari -- Connecting roles and purposes in undergraduate embedded mentoring / Keaton Kirkpatrick -- Leaky bodies and connective tissues: a cripped metho-epistemology of mentoring / Leslie R. Anglesey and Melissa Nicolas -- Testimonio as a methodology for examining marginalized experiences with mentorship / Michelle Flahive -- A post-arrival mentorship that's not a mentorship: mediated discourse theory and the ecological approach to learning over time and place / Aurora Matzke and John Paul Tassoni.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Methodology; Writing centers -- Methodology; Mentoring -- Study and teaching (Higher); Methodology -- Study and teaching (Higher); Mentoring in education